2007
DOI: 10.1088/0953-2048/20/3/023
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced high-field performance in PLD films fabricated by ablation of YSZ-added YBa2Cu3O7−xtarget

Abstract: YBa2Cu3O7−x+Y2O3-stabilized ZrO2 (YBCO+YSZ) mixed films were prepared on SrTiO3/MgO substrates by pulsed-laser deposition from a YBCO target with a thin YSZ sector on top. The Jc at 77 K for the mixed YBCO+YSZ thin film was enhanced. The Jc at 77 K for the pure film and the mixed YBCO+YSZ thin film were 1.46 and 1.95 MA cm−2 (self field) (and 0.09 and 0.28 MA cm−2 (, B = 5 T)), respectively, even when both films were prepared using the same deposition conditions. The maximum pinning force of a doped film (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
57
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 24 publications
3
57
0
Order By: Relevance
“…To form Y 2 O 3 (YO) doped and BaZrO 3 (BZO) doped YBCO films, a "surface modified method" was used [3]. The same YBCO target was modified: a thin (0.5 mm thick) and narrow (area of about 2 ÷ 2.5 % of the surface area of the YBCO target) YO (or YSZ) sector was cut from YO (or YSZ) single crystal, respectively, and stuck on the YBCO target by silver paint.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To form Y 2 O 3 (YO) doped and BaZrO 3 (BZO) doped YBCO films, a "surface modified method" was used [3]. The same YBCO target was modified: a thin (0.5 mm thick) and narrow (area of about 2 ÷ 2.5 % of the surface area of the YBCO target) YO (or YSZ) sector was cut from YO (or YSZ) single crystal, respectively, and stuck on the YBCO target by silver paint.…”
Section: Methodsmentioning
confidence: 99%
“…Below we refer to experimental results obtained for a "pure" ~310 nm thick film (YBCO), a ~294 nm thick film with YO inclusions (YBCO YO), and for a ~317 nm thick film containing BZO nanorods, resulting from the reaction between ZrO 2 and YBCO while fabricating the film [3], and preferentially oriented along the c axis (YBCO BZO). In YBCO YO round-shaped YO inclusions of a mean diameter of 6−8 nm were randomly distributed (with a mean spacing of about 12 nm) and dispersed throughout the entire film thickness.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…19 More than an order of magnitude improvement in J c was observed in 300 nm thick film samples as compared to YBCO samples of similar thickness at 5 T, H / /c. 10 Recently Mele et al 12 compared the performance of YBCO+ BZO and YBCO+ BSO thin films as well and showed that the films with BSO have higher pinning force. However, thick film ͑Ͼ2 m͒ performance in YBCO+ BSO films at high fields was not previously discussed.…”
Section: -13mentioning
confidence: 99%
“…The minimum J C generally occurs under a magnetic field applied perpendicularly to the film owing to the anisotropy of superconductivity in RE123. To increase this minimum J C , the introduction of pinning centers into RE23 superconducting films to stop the magnetic flux has been attempted, and the subsequent enhancement of J C under a magnetic field has been investigated [2,3,4,5,6,7,8]. The pinning centers with controlled shapes, sizes and densities are called artificial pinning centers (APCs).…”
Section: Introductionmentioning
confidence: 99%